Reutilización del desperdicio generado por el corte y la fabricación de la madera plástica (2015)
The company MADERPLASTIC SAS transforms industrial and municipal waste for the manufacture of plastic wood, production is being generated large amounts of waste which are not standardized as production orders are totally different depending on the client, storage this cake was creating a mountain of waste.